2016
DOI: 10.1016/j.ocemod.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Submesoscale circulation in the northern Gulf of Mexico: Surface processes and the impact of the freshwater river input

Abstract: !The processes and instabilities occurring at the ocean surface in the northern Gulf of Mexico are investigated with a regional model at submesoscale-permitting horizontal grid resolution (i.e., HR with dx = 1.6 km) over a three-year period, from January 2010 to December 2012. A mesoscale-resolving, lower resolution run (LR, with dx = 5 km) is also considered for comparison. The HR run is obtained through two-way nesting within the LR run. In HR quantities such local Rossby number, horizontal divergence, verti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 68 publications
7
82
0
Order By: Relevance
“…Submesoscale processes over the NWGoM have been shown to exhibit a primary energetic peak in the winter and a secondary energetic peak in the summer (Luo et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Submesoscale processes over the NWGoM have been shown to exhibit a primary energetic peak in the winter and a secondary energetic peak in the summer (Luo et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, ambient slope currents (MKE) were averaged over a four month period, blurring larval entrainment and cross isobath transport on short time scales. Submesoscale processes (Luo et al 2016) may be important at the shelf break, but will not be captured within the scales of this study.…”
Section: A B Discussionmentioning
confidence: 99%
“…For example, it has been shown that submesoscale eddies have been shown to contribute to the onset of plankton blooms by restratifying the mixed layer in early spring (Mahadevan et al, 2012), submesoscale filaments around the eddy perimeter subduct large amounts of POC during spring blooms at high latitudes (Omand et al, 2015), and submesoscale fronts can converge effectively and quickly any floating material into 'lines' a few meters in width and up to several kilometers in length (Zhong et al, 2012;Mahadevan, 2016). Submesoscale fronts are particularly abundant in the northern Gulf of Mexico (GoM) where surface density gradients are fueled by the energetic mesoscale field and also by the abundant riverine input (Zhong et al, 2012;Luo et al, 2016;Barkan et al, 2017a).…”
Section: Research Articlementioning
confidence: 99%
“…In between mesoscale structures, a large number of submesoscale circulations such as vorticity filaments and small vortices, on a spatial scale of 1-10 km and with a lifespan of days, can be seen, particularly in September. Submesoscale processes extract available potential energy from the mixed layer (Molemaker et al, 2005;McWilliams, 2008) through processes such as frontogenesis and mixed layer instabilities (Thomas and Ferrari, 2008;Luo et al, 2016;Barkan et al, 2017a). Submesoscale features are stronger and more numerous when more available potential energy can be extracted.…”
Section: Mesoscale and Submesoscale Circulations In March/ April And mentioning
confidence: 99%